Assessment of higher order thinking among preschool children - Siti Yusrina, binti Yusof (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This research aims to develop a learning module intended to develop children's higher order thinking skills and directly aim to test the effectiveness of the module in shaping and boosting their thinking skills. The development of the module emphasized on child centered learning. This research was an action research as the modules build were implemented in the preschool learning. The 22 participants were purposively selected from preschool children of five to six years old. The result showed that the module gives positive effect towards children's higher order thinking but the time elongation to further validate the result need to be taken. It is hoped that his research can contribute towards many higher order thinking modules development that will benefit to the society.